Insight into Interfacial Charge Transfer during Photocatalytic H2 Evolution through Fe, Ni, Cu and Au Embedded in a Mesoporous TiO2@SiO2 Core‐shell. Issue 12 (26th May 2022) - Xu, Qian; Knezevic, Marija; Laachachi, Abdelghani; Franger, Sylvain; Colbeau‐Justin, Christophe; Ghazzal, Mohamed Nawfal
Abstract: The efficiency of charge transfer at the interface of transition metals loaded on TiO2 as well as the active reduction site undoubtedly define the kinetics of H2 production. Here, we report the interfacial charge process of various transition metals (Fe, Ni, Cu, and Au) embedded in mesoporous core‐shell nanostructures, which provides further insight into the photocatalytic H2 evolution. Au was found to be the most active cocatalyst for the H2 evolution. Au nanoparticles (NPs) collect electrons and become a very efficient reduction site, promoting both charge separation and H2 evolution. The scavenging capacity of Au was found to be the highest compared to other NPs. Cu(I), which is as active as Au, but at a higher loading, also shows an ability for electron scavenging and acts as an active site under UV excitation, or rather injects electrons into the TiO2 conduction band under visible excitation. Ni(II) NPs were found to be involved in charge‐carrier separation through hole collection and their contribution to hydrogen evolution is expected to be limited to visible absorption and electron injection. The same behavior occurs with Fe(III), however, it is less efficient for H2 generation due to the weak charge‐carrier lifetime. We show that only Cu(I) could compete with noble metals such as Au, presenting electron‐scavenging behavior. Understanding the charge‐carrier dynamics will help design a very efficient system for photocatalytic H2 generation system. Abstract : Scavenging : Understanding the operating process of charge carriers will help design a higher capability of electron scavenging for a very efficient photocatalytic H2 generation system. Here, we report the interfacial charge carrier process for various transition metal nanoparticles and show that only Cu(I) could compete with Au.